Nový magistrát města Brna - Syniuk, Kateryna (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Diplomová práce zpracovává nový městský magistrát v Brně a navazuje na urbanistickou studii zpracovanou Téma diplomové práce je zasazeno do jižní části města Brna, hranice řešeného území tvoří ulice Úzká a síť budoucích ulic čtvrti Trnitá. Budova magistrátu, řešená v diplomové práci, je složená z dvou objektu s administrativním provozem. Parter magistrátu je částečně doplněn o komerci. Dispozičně jsou jednotlivé stavby řešeny jako trojtraktová a pětitraktová kancelářské budovy. Hlavní budova magistrátu je navržená včetně klientské přepážkové haly, umístěné v atriu. Nosný systém objektu je navržen jako monolitický železobetonový skelet. Stavba využívá moderní energetické systémy, jako je tepelné čerpadlo země-voda. Objekt je zastřešen plochou střechou se zelenou střechou.

This diploma thesis addresses the design of Brno city new municipal building and is based on a previously developed urban planning study. The topic of the thesis is situated in the southern part of the city of Brno, on a site defined by Úzká Street and the network of future streets of the Trnitá district. The city hall building proposed in the thesis consists of two separate administrative buildings. The ground floor of the complex partially includes commercial spaces. The buildings are designed as three- and five-bay office structures. The main administrative building includes a client hall located within a central atrium. The load-bearing system is designed as a monolithic reinforced concrete frame, providing both structural efficiency and architectural flexibility. The building uses modern energy systems, including a ground-source heat pump (water-to-water system). The roof is designed as a flat roof, partially covered with a green roof system to improve microclimate performance and enhance the sustainability of the building.
Brno City New Municipal Building
Keywords: Magistrát; radnice; administrativní budova; kanceláře; atrium; město; Brno; kamenný obklad; zelená střecha.; City Hall; Municipal Building; Administrative Building; Offices; Atrium; City; Brno; Stone Cladding; Green Roof